Partisipasi Anggota Kelompok Wanita Tani Pangan Sari pada Program Kawasan Rumah Pangan Lestari (Studi kasus di Dusun Cengkilung, Desa Peguyangan Kangin, Kecamatan Denpasar Utara, Kota Denpasar) - NI LUH PUTU CANDRA DEWI; WAYAN SUDANA; I GEDE SETIAWAN ADI PUTRA (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2015)
Abstract The Participation of Group Members of Women Farmers of Pangan Sari in the Program of Sustainable Food House Area (Case Study in Cengkilung Sub Village, Peguyangan Kangin Village, The Sub-District of North Denpasar, Denpasar City). The Ministry of Agriculture has developed the Sustainable Food House Area Program in the Women Farmers Group of Pangan Sari. To develop the programs, it needs participation. The aims of the research are to determine: (1) the level of participation of members;(2) to describe the obstacles faced the Women Farmers Group of Pangan Sari. The study was conducted in Cengkilung sub village. The research location was determined intentionally with the population of the Women Farmers Group of Pangan Sari members of 20 people and they were all used as the respondents defined by census method. Data were analyzed by using descriptive qualitative ordinal scale (Likert). The average level of participation based on the forms of participation which were: financial, material, service and moral participation of 86,67% which considered as a very high category. The obstacles faced (1) the technical aspects: limitations of nursery village; (2) the economic aspect: land supply remains of nursery village and capital limitation in fulfilling the crop production facilities; (3) the social aspect: no problem raised because the group member have good relationship with the goverment, inter-group members and outside parties. The participation of members is very high, then the program can be developed in the field of marketing, making an agreement with the owner of the land or using one of member’s land as nursery village and more technical guidance related to organic cultivation techniques. Keywords: participation, sustainable food house area, group, women farmers.